Analysis of Community Participation in Paying Motor Vehicles Tax through e-Samsat Service during Covid Pandemic at the Samsat Office in Jakarta Utara - Totok Priyono; Fika Wulandari; Eka Rofiyanti; Dwi Agustina (Yayasan Ilomata, 2022)
Taxes are the largest source of state revenue to meet routine state expenditures or finance national development. In the increasingly rapid development of information technology, various innovations have been created to facilitate human life. One of them is in the service sector. To improve the quality of tax services, the government created an online tax payment service system called Electronic Samsat or E-SAMSAT. E-SAMSAT is considered a solution for tax payment services, especially motor vehicle taxes, during the COVID-19 pandemic because it is faster and there is no need to queue, such as direct tax payment services at the SAMSAT office. However, unfortunately, many taxpayers have not taken advantage of these services. This is due to the administrative system, which is considered complicated, and people's digital literacy is still low. The method used in this research is descriptive qualitative to describe this research in-depth. The results of this study are public participation in the payment of Motor Vehicle Taxes through E-Samsat Services during the Covid Pandemic at the North Jakarta Samsat Office, judging from the six participation criteria presented by Mangkunegara, that has gone quite well. The community as taxpayers has participated in implementing the E-SAMSAT service system. However, unfortunately, not all people can access these services. The service procedure is quite long, and the people's digital literacy level is still low, causing the community not to be able to take full advantage of the service system.